Методика дослідження форми деревного стовбура з накладеною кроною та без неї - Kichura, Volodymyr; Kichura, Anastasia (Ukrainian Research Institute of Forestry and Forest Melioration named after G. M. Vysotsky (URIFFM), 2025)
Introduction The shape of a tree trunk significantly influences the volume and quality of industrial assortments derived from harvested trees. Consequently, the study of trunk shape has remained a central topic in forest mensuration for over a century. Traditionally, research has focused on the shape of trunks without the crown, a practice that continues today. However, investigations into trunk shape with the crown superimposed are relatively recent and still emerging. Comparative studies of trunk shapes with and without an overlapping crown have shown that shape variability primarily depends on the proportion of crown volume relative to the total volume of the tree’s above-ground parts. Specifically, an increase in the crown’s relative volume tends to correlate with increased tapering of the trunk, and vice versa. This relationship can be analyzed through a specially developed methodology that satisfies the unique requirements for collecting, measuring, and processing experimental data. This method is intended for comparative analysis of trunk shape in two configurations: (1) without the crown, and (2) with the crown superimposed. Materials and Methods The methodology was developed using generalized data from a substantial sample of sample trees: 233 trees for trunk shape analysis with a superimposed crown, and over 1,000 trees for assessing average trunk shape without the crown. The approach combines traditional forest mensuration techniques with mathematical methods, including direct inductive and deductive reasoning, mass observation, and averaging. Results The methodology outlines procedures for data collection, measurement, and processing. Key components include: criteria for selecting trees for measurement, general measurement protocols, field procedures for measuring actual trees, data processing techniques to derive results for trunk shapes both with and without superimposed crowns..A distinctive feature of the method is its use of stump volume formulas to convert volumetric data into linear parameters. This enables a mathematical expression of the crown's influence on trunk shape. The method allows the precise identification of characteristic points on the S-shaped portion of the trunk, both with and without the crown. Conclusions The proposed methodology enables the characterization of trunk shape with and without a superimposed crown and provides insights into the distribution of the volume along the tree height. 4 Figs., 6 Refs.